Nonlinear modal analysis of mechanical systems with frictionless contact interfaces - Laxalde, Denis; Legrand, Mathias (Computational mechanics, 2011)
This paper explores mechanical systems undergoing unilateral frictionless contact conditions in the framework of nonlinear modal analysis. The nonlinear eigenproblem is formulated in the frequency domain through the minimization of a Rayleigh quotient subject to non-penetration inequality constraints. An additional equality constraint is introduced for normalization purposes. The resulting constrained minimization problem is then solved using an augmented Lagrangian strategy. Two applications are proposed: a thin longitudinal rod in unilateral contact with a rigid obstacle and a turbomachinery compressor blade in contact with a rigid casing. The first application illustrates the complexity of the nonlinear modal characterization of a system experiencing unilateral contact conditions while the second demonstrates the applicability of the proposed approach to large-scale mechanical systems involving non-smooth nonlinear terms.